Explaining PISA 2022 Achievement Disparities through Educational Policy and Learning Culture: A Macro-Comparative Analysis of Indonesia, Brunei Darussalam, Portugal, and New Zealand - Uun Purnasih; Iman Subasman; Iis Nuraeni; Suwarno AS; Dirno; Rd. Khilal; Hanifah Amalia (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Disparities in PISA 2022 performance across nations suggest that determinants of educational quality extend beyond economic capacity alone. This study aims to analyze the underlying factors of PISA 2022 performance gaps by comparing Indonesia, Brunei Darussalam, Portugal, and New Zealand from a macro-comparative education perspective. Grounded in Arnove et al.'s Global–Local Dialectic theory, the study employs secondary documentary data—including OECD PISA 2022 reports, national education policy documents, regulations, government reports, and peer-reviewed articles—analyzed through qualitative comparative content analysis involving data reduction, thematic coding, and cross-case comparison. Findings indicate that PISA performance differences are shaped by the interaction between structural policy capacity and culturally embedded learning practices. New Zealand and Portugal demonstrate resilience through policy consistency and learner autonomy; Brunei Darussalam benefits from centralized governance and substantial fiscal investment; Indonesia continues to experience systemic fragmentation, uneven policy implementation, and a literacy culture yet to become functional academic practice. Evidence-based policy consistency and cultivating functional learning cultures constitute strategic foundations for improving educational quality.